A suggested approach to once-daily aminoglycoside dosing. - Begg, E J (1995)
1. Once-daily aminoglycoside dosing has many advantages and has been widely advocated. However, existing guidelines for methods of administration and monitoring are non-specific and may lead to excessive dosing. 2. The traditional approach of aiming for target peak and trough concentrations is not appropriate for once-daily dosing. 3. A method is proposed which uses a target area under the concentration-time curve (AUC) for the aminoglycoside based on the 24 h AUC that would result with conventional dosing. This method requires measurement of two drug concentrations, one approximately 0.5 h after the end of the infusion and another at a later time (6-22 h) depending on renal function. 4. A simpler, graphical method is also proposed for patients with normal renal function, which requires the measurement of a single concentration at a time between 6 and 14 h. 5. Both methods are likely to be safer than existing guidelines.